Flexural strength and hardness of reline and denture base acrylic resins after different exposure times of microwave disinfection - Ribeiro, Daniela Garcia [UNESP]; Pavarina, Ana Cláudia [UNESP]; Machado, Ana Lucia [UNESP]; Giampaolo, Eunice Teresinha [UNESP]; Vergani, Carlos Eduardo [UNESP] (My University, 2008)
Objectives: To evaluate the effect of microwave disinfection on the flexural strength and Vickers hardness of 4 autopolymerized resins (Kooliner [K], Tokuso Rebase Fast [T], Ufi Gel Hard [U], and New Truliner [N]) and 1 denture base resin (Lucitone 550 [L]). Method and Materials: For each material, 48 specimens (64 × 10 × 3.3 mm) were made and divided into 6 equal groups (n = 8). In the control group, specimens were untreated. Before testing, specimens were immersed in 200 mL of distilled water and submitted to disinfection for 1 of the following irradiation times: 1, 2, 3, 4, or 5 minutes. The irradiation procedure was performed twice. The flexural strength was determined using a testing machine MTS-810 and measurements of Vickers hardness were made on Micromet 2100. The values were submitted to ANOVA and Tukey's test (P = .05). Results: The K material showed a significant increase (P = .0010) in flexural strength following 5 minutes of disinfection compared to control specimens. The flexural strength mean values of materials T, U, and N were not significantly affected (P > .05) by disinfection. Compared to the control group, the K material showed a significant increase in hardness (P < .001) following disinfection for 3, 4, and 5 minutes. For material U, disinfection for 4 and 5 minutes produced specimens with significantly increased hardness values (P < .001) compared to the control group. For material N, disinfection for 5 minutes resulted in significantly higher hardness values (P < .001) than the control group. Conclusion: Regardless of the irradiation time, the flexural strength and hardness of the materials evaluated were not detrimentally affected by microwave disinfection.
Keywords: Acrylic resins; Cross infection; Disinfection; Flexural strength; Hardness; Microwave